Manifold Destiny Arabs at an American Crossroads of Exceptional Rule - Karam, John Tofik (Vanderbilt University Press, 2021)
At the border where Brazil, Paraguay, and Argentina meet under the scrutiny of the US and Mercosur (the large South American trade bloc), Arabs have long fulfilled what author John Tofik Karam calls a "manifold destiny." Karam casts Lebanese, Palestinians, and Syrians at this American border as circumstantial protagonists of a hemispheric saga.br /br /For the more than six decades since they started settling at the trinational border between Brazil, Paraguay, and Argentina, Arabs have animated the hemisphere. Their transnational economic and social projects reveal a heretofore unacknowledged venue of exceptional rule in which the community accommodates and abides multiple states' varied suspensions of norms and laws. Arabs set up businesses and community centers at the border under authoritarian military governments between the 1950s and 1980s; thereafter, when denied full democratic enfranchisement, they instead underwent increasing surveillance from the 1990s to today. Karam reveals an unfinished history of exceptional rule that Arabs accommodate from an authoritarian past to a counterterrorist present.br /br /Karam's riveting account draws on anthropological and historical research from each side of this trinational South American border, as well as from the US-where government bureaucrats still suspect Arabs at the border of would-be-terrorist subversion. Offering a fresh understanding of the hemisphere, emManifold Destiny/em brings the transnational turn of Middle Eastern studies to bear upon the fields of American studies, Brazilian studies, and Latin American studies.